Minat Prestasi Olahraga E-Sport di Sekolah Menengah Kejuruan Negeri 1 Pugaan Kabupaten Tabalong - Muhammad Rizaldi; Rahmadi Rahmadi; Arie Rakhman (Jurnal Keolahragaan, 2025)
The development of increasingly advanced technology, several new sports branches have emerged that utilize the latest model, namely electronic media which is often called E-Sport. Then there are many students of SMK Negeri 1 Pugaan who play online games. The purpose of this study was to determine how students' achievement interests are in E-Sport Mobile Legends Bang-Bang Division at SMK Negeri 1 Pugaan. Quantitative descriptive research using survey methods. The research variables are students' achievement interests using the population of SMK Negeri 1 Pugaan. A sample of 41 students using the proportionate stratified random sampling technique. Data collection using observation, documentation and questionnaires. With instruments in the form of questionnaires. Descriptive statistical data analysis percentage as a data analysis technique. The results of this study indicate that the interest in e-sport sports achievements at SMK Negeri 1 Pugaan, Tabalong Regency in internal factors (interest, needs, willingness, attention, activities, hobbies/recreation) affects the high interest of students by producing the largest value of 70.73% in the attention sub-indicator. Meanwhile, in external factors (environment/social, facilities) the results showed that 60.97% influenced the high interest of students in the facilities sub-indicator, in this case influencing the interest in e-sports achievements at Pugaan 1 State Vocational School, Tabalong Regency.